Nanostructural study of silicon-cobalt/nitrogen-doped reduced graphene oxide composites by electron microscopy for using as anode material in lithium-ion batteries - Thanapat Autthawong (2018)
© 2018 Trans Tech Publications, Switzerland. Silicon-cobalt nanocomposites on NrGO, Si-Co/NrGO, were synthesized by the modified polyol method. Rice husk was used as the silicon source. The composites were primarily characterized by x-ray diffraction, scanning electron microscopy, and transmission electron microscopy equipped with energy dispersive spectroscopy. The small-sized particles of the silicon-cobalt product were effectively distributed on the NrGO. Finally, these anode materials were tested in lithium-ion batteries by haft-coin cell assembly. Electrochemical properties were measured and the result showed an initial capacity of 975 mAh g-1 . This material is expected to be used as a high-performance anode, suitable for the next generation of anode materials in lithium-ion batteries.